2015
DOI: 10.3346/jkms.2015.30.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Advance Directives in a Hospice Center

Abstract: To protect patient autonomy when confronting death, the importance of advance directives (ADs) has recently became an issue and gradually accepted in Korea. However, in real practice, ADs were not completed by patients but their families in most cases. To analyze the current situation of performing ADs, we reviewed medical charts of 214 terminal cancer patients admitted to the hospice center from October 2012 to September 2013. Seventy-six (35.5%) patients completed ADs. All ADs were completed by patients them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 11 publications
1
11
1
Order By: Relevance
“…The survival or mortality rate can be different in a wide range of diseases, and therefore patients may have different confidence in overcoming the disease. Furthermore, contrary to our study, in the study by Kong et al . most terminal cancer patients did not want to receive any invasive medical interventions to sustain life.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…The survival or mortality rate can be different in a wide range of diseases, and therefore patients may have different confidence in overcoming the disease. Furthermore, contrary to our study, in the study by Kong et al . most terminal cancer patients did not want to receive any invasive medical interventions to sustain life.…”
Section: Discussioncontrasting
confidence: 97%
“…In Germany, 18% of cancer patients, 19% of healthy people, and 28%–31% hematology and oncology outpatient patients had signed ADs . In Korea, 35.5% of patients in a Hospice Center completed ADs, and in the report by White et al . 14% of the Australian population had ADs .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In particular, palliative sedation may be introduced during a palliative care advance care planning, in order to help patients and their family members to understand what palliative sedation is and to express their opinions and possible concerns with regard to this practice. Although several studies showed that most patients with cancer preferred the use of palliative sedation (Kong, An, & Kim, ; Miccinesi, Bianchi, Brunelli, & Borreani, ; Pautex, Notaridis, Déramé, & Zulian, ), there are patients who might prefer to die in a state of consciousness (Miccinesi et al, ). In addition, since advance care planning discussions “should match how ready the person is to talk about her or his medical care” (Sudore et al, ), the adaptation of advance care planning according to the readiness of the individual is recommended (Rietjens et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies showed that most patients with cancer preferred the use of palliative sedation (Kong, An, & Kim, 2015;Miccinesi, Bianchi, Brunelli, & Borreani, 2012;Pautex, Notaridis, Déramé, & Zulian, 2010), there are patients who might prefer to die in a state of consciousness . In addition, since advance care planning discussions "should match how ready the person is to talk about her or his medical care" , the adaptation of advance care planning according to the readiness of the individual is recommended .…”
Section: Discussionmentioning
confidence: 99%